Sluggish information diffusion and monetary policy shocks - Gomes, O.; Mendes, V. (Economics Bulletin, 2011)
The sticky-information model appeared in order to offer a more empirically consistent view on the effects of monetary policy than the one provided by the benchmark sticky prices setup. Such inattentiveness framework was built on the assumption that current decisions are mainly based on past expectations about the current state of the economy. In this note, we propose an explanation for information stickiness that goes beyond the simple idea of infrequent updating of expectations. The suggestive new feature is that contemporaneous decisions will depend on a process of information diffusion that is triggered by the relation between two rational players: the profit maximizing media industry and the private agents, who seek information in order to update prices.